Indirect optimization for finite thrust orbit transfer and cooperative rendezvous using an initial guess generator. Issue 6 (15th March 2023) - Ren, Fei; Li, Ruichuan; Xu, Jikang; Feng, Chenyu
Abstract: In this paper, the finite thrust nonplanar transfer and cooperative rendezvous are investigated. The indirect method is adopted in the optimization process. The energy-optimal to fuel-optimal continuation is performed by using the homotopy method. An initial guess generator (IGG) is designed based on a simplified dynamical model to overcome the difficulty in providing the initial guess. Some reasonable simplifications on the dynamical model are applied based on the near-circular near-coplanar transfer. The initial guess can be obtained by analytically solving a system of linear equations. Therefore, the IGG has high computational efficiency. Moreover, the terminal time and state are estimated by IGG to deal with the cooperative rendezvous problem. Numerical examples are presented and the validity of the "IGG-Homotopy" combined algorithm is verified.